Gestión de Riesgos Mayores en el Auditorio de la Universidad Nacional de Chimborazo: Plan de Emergencia. - Verdesoto Espinoza, Edison Miguel (2015)
The present thesis deals with the prevention, control and mitigation that can produce a potential danger, and how to act after this will raise in the Theater of the National University of Chimborazo. It is necessary and essential to the development and implementation of an emergency plan taking into account the size and the activity performed and the potential presence of persons outside the same, which will analyze the possible emergency situations and take necessary measures in first aid, firefighting and evacuation of workers, appointing for that personnel responsible for implementing these measures and checking periodically, if necessary, correct operation. This emergency plan proposes to establish the institutional response capacity of the National University of Chimborazo to an incident Emergency Plan is a set of measures to deal with risk, minimizing the effects on people and goods may arise and ensuring the safe evacuation of the occupants. Data collection of construction, materials used, infrastructure, and background of theater, which served for the application of methods and formats handled was performed.